2018
DOI: 10.1186/s12936-018-2526-8
|View full text |Cite
|
Sign up to set email alerts
|

Household costs and time to treatment for children with severe febrile illness in rural Burkina Faso: the role of rectal artesunate

Abstract: BackgroundCommunity health workers (CHWs) were trained to identify children with malaria who could not take oral medication, treat them with rectal artesunate (RA) and refer them to the closest healthcare facility to complete management. However, many children with such symptoms did not seek CHWs’ care. The hypothesis was that the cost of referral to a health facility was a deterrent. The goal of this study was to compare the out-of-pocket costs and time to seek treatment for children who sought CHW care (and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Thirdly, the distance traveled to health facilities was associated with health expenditures. In a study on households' costs to severe malaria treatment in rural Burkina Faso, it was found that the main driver of the cost difference was the transportation [7]. Findings from a study in rural Bangladesh on the use of facility-based maternity services, showed that for each additional kilometer, the cost increased by $0-13 for antenatal care, $0-44 for delivery, and $0-11 for postnatal care [14].…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, the distance traveled to health facilities was associated with health expenditures. In a study on households' costs to severe malaria treatment in rural Burkina Faso, it was found that the main driver of the cost difference was the transportation [7]. Findings from a study in rural Bangladesh on the use of facility-based maternity services, showed that for each additional kilometer, the cost increased by $0-13 for antenatal care, $0-44 for delivery, and $0-11 for postnatal care [14].…”
Section: Discussionmentioning
confidence: 99%
“…Last, one could dispute our inability to check the common trend assumption, since no nation-wide data are available to check the development of OOPE among different groups over time. Based on existing literature reporting OOPE at different points in time and across locations, 19 , 27 , 74 , 75 we felt confident to assume that in the absence of the gratuité , OOPE would have followed the same trend for individuals below and above 5 years of age. Similarly, analysis of HMIS data confirms equal utilization rates.…”
Section: Discussionmentioning
confidence: 99%